Investigating the Causes of War and the Conditions of Peace: Measuring Military Power and Testing Structural Realism in the South China Sea - Abramowicz, Victor (Curtin University, 2022)
This dissertation investigates if nations are generally driven towards war or peace; how countries’ individual predispositions towards violence can be identified; and when conflict is likeliest to occur, based on balances of power. These questions are addressed through a mixed qualitative- quantitative test of Defensive Realism, Offensive Realism, and Balance of Power and Power Transition Theory. The outcomes show States generally favour peace; assessing nations’ strategies reveals their predispositions; and that power imbalances enable conflict.